Carbon-iron-hybrid carbon catalyst as well as preparation method and application thereof

The carbon-iron-hybrid carbon catalyst was prepared by hydrothermal method, which solved the problem of slow kinetics and poor stability of electrocatalysts in electrochemical water cracking, and achieved the electrocatalytic water decomposition effect with low overpotential and high stability.

CN119145003APending Publication Date: 2024-12-17NORTHWEST NORMAL UNIVERSITY
View PDF 0 Cites 0 Cited by

Patent Information

Application Number
CN202411331434.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-24
Publication Date
2024-12-17

AI Technical Summary

Technical Problem

In electrochemical water cracking, existing electrocatalysts have problems such as slow kinetics, unsatisfactory overpotentials and poor stability. Especially, high-active single-atom catalysts are prone to failure in long-term use, making it difficult to achieve efficient and long-lasting water decomposition.

Method used

The carbon-iron-hybrid carbon catalyst is prepared by hydrothermal method. By embedding atomic iron active species into carbon spherical materials and adding nitrogen source for doping, the interfacial C-Fe-N coupling moiety is formed to regulate the electrons of the catalyst. Structural and active species are exposed to improve catalyst activity and stability.

Benefits of technology

It achieves low overpotential, low electrochemical impedance and significant stability, enhances the activity and durability of electrocatalytic water decomposition, and enhances the catalyst through the interface C-Fe-N coupling effect and unique local coordination microenvironment. performance.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure CN119145003A_ABST
    Figure CN119145003A_ABST
Patent Text Reader

Abstract

The invention provides a carbon-iron-hybrid carbon catalyst as well as a preparation method and application thereof, and belongs to the technical field of energy and new materials. The preparation method comprises the following steps: embedding atomic-scale iron active species into carbon in situ by adopting a hydrothermal method to obtain a carbon-iron product, and then adding a nitrogen source for doping to obtain the carbon-iron-hybrid carbon catalyst. According to the invention, the intrinsic electronic structure of the catalyst and exposure of active species are adjusted by constructing a unique interface C-Fe-N element, so that the activity of the catalyst is improved. And meanwhile, a C-Fe-N coupling element formed on the interface can obviously protect the corrosion resistance of the electrolyte of active species, so that the durability of the catalytic reaction is realized. The carbon-iron-hybrid carbon catalyst prepared by the invention can be used for electro-catalytic water decomposition.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention relates to the technical field of energy and new materials, and in particular to a carbon-iron-hybrid carbon catalyst and a preparation method and application thereof. Background Art

[0002] As a clean alternative energy carrier, hydrogen has attracted extensive attention due to its environmentally friendly characteristics and zero carbon emission. Electrochemical water splitting is considered to be a promising and feasible strategy for large-scale hydrogen production due to its simple development process, low pollution, and superiority over other methods such as coal gasification and methane distillation modification.

[0003] Electrochemical water splitting consists of two opposing chemical reactions: the cathode hydrogen evolution reaction (HER) and the anode oxygen evolution reaction (OER). In general, effective water splitting requires excellent electrocatalysts, which improve the slow kinetics, unsatisfactory overpotential and poor stability. The most widely used electrocatalysts for OER are precious metal-based catalysts, such as platinum (Pt), rubidium (Ru), iridium (Ir), Pt / C, RuO2 and IrO2. However, the large-scale production of these precious metal-based materials is limited due to scarcity and high cost. Therefore, many alternative materials with excellent OER performance have been developed, which are abundant and inexpensive on Earth. They have been used to design economically viable catalysts, including oxides, sulfides, selenides, nitrides, carbides, and phosphates, and have made significant progress. Although economically viable catalysts have been designed, the actual performance of these alternative catalysts must be improved compared with precious metal catalysts. Transition metal single-atom catalysts (TM-SACs) exhibit excellent electrocatalytic performance due to their unique isolated atom characteristics, abundant active centers, remarkable atom utilization, and effective unsaturated coordination environment. However, problems related to the stability of isolated single metal centers, precise control of local single-atom active sites, and low utilization of active sites in mixed catalyst systems have plagued the preparation of highly active single-atom catalysts (SACs). In particular, the effective performance of single atoms in electrochemical reactions is closely related to their atomic structure, local microenvironment, number of single atoms, number of coordinated atoms, and their interaction with substrates at the subnanometer scale. Other factors that significantly improve the performance include the regulation of electronic structure and the optimization of promoting electron-electron coupling between single metal atoms and supports, coordinated atoms, active layer electron-electron coupling, electron spin adaptation, and adsorption energy of reaction intermediates. However, the practical applications of many SACs are still plagued by long-term stability issues during electrochemical reactions. Therefore, it has been a challenge to develop single-atom electrocatalysts (SACs) with high activity and stability for electrocatalytic water splitting. Summary of the invention

[0004] The purpose of the present invention is to provide a carbon-iron-hybridized carbon catalyst and a preparation method and application thereof. The prepared carbon-iron-hybridized carbon single-atom catalyst has high activity and stability and can be used for electrocatalytic water decomposition.

[0005] In order to achieve the above-mentioned object of the invention, the present invention provides the following technical solutions:

[0006] The present invention provides a method for preparing a carbon-iron-hybrid carbon catalyst, comprising the following steps:

[0007] The carbon ball material, the iron source, the surfactant and the first solvent are mixed and subjected to a first hydrothermal reaction to obtain a carbon-iron product;

[0008] The carbon-iron product, a nitrogen source, a carbon source and a second solvent are mixed and subjected to a second hydrothermal reaction to obtain a carbon-iron-hybrid carbon catalyst.

[0009] Preferably, the iron source includes ferric chloride; and the surfactant includes hexadecyltrimethylammonium bromide or polyvinylpyrrolidone.

[0010] Preferably, the mass ratio of the carbon ball material, the iron source and the surfactant is 0.05-0.2:0.3-1.6:0.15-0.6.

[0011] Preferably, the temperature of the first hydrothermal reaction is 160-200° C., and the time is 6-12 hours.

[0012] Preferably, the carbon source includes glucose or sucrose; and the nitrogen source includes dicyandiamide.

[0013] Preferably, the mass ratio of the carbon-iron product, the nitrogen source and the carbon source is 0.025-0.1:0.05-0.2:0.2-0.8.

[0014] Preferably, the temperature of the second hydrothermal reaction is 160-200° C., and the time is 2-6 hours.

[0015] The present invention provides a carbon-iron-hybrid carbon catalyst prepared by the preparation method described in the above technical scheme.

[0016] The present invention provides the use of the carbon-iron-hybrid carbon catalyst described in the above technical solution in electrocatalytic water decomposition.

[0017] The present invention provides a method for preparing a carbon-iron-hybrid carbon catalyst, wherein an atomic-level iron active species is in situ embedded in carbon by a hydrothermal method to obtain a carbon-iron product, and then a nitrogen source is added for doping to obtain a carbon-iron-hybrid carbon catalyst. The present invention adjusts the intrinsic electronic structure of the catalyst and the exposure of the active species by constructing a unique interface C-Fe-N motif, thereby improving the activity of the catalyst. At the same time, the C-Fe-N coupling motif formed at the interface can significantly protect the electrolyte corrosion resistance of the active species, thereby achieving the durability of the catalytic reaction.

[0018] The carbon-iron-hybrid carbon catalyst prepared by the present invention has an interfacial iron single-atom electronic bridge, and the carbon atom in the inner core is coupled with the nitrogen atom in the outer shell through the iron atom, presenting an iron-bridge core-shell nanosphere morphology, having a rich interface, and the catalyst exhibits a low overpotential and low electrochemical impedance. It exhibits significant activity and excellent stability in the difunctional decomposition of water, which is due to the strong coupling effect between C-Fe-N at the interface, forming a unique single-atom C3-Fe-N local C-Fe-N coordination microenvironment at the interface, enhancing the exposure and charge transfer of the active site, reducing the adsorption energy barrier of the intermediate, and can be used for electrocatalytic water decomposition.

[0019] The present invention uses theoretical calculations and synchrotron radiation to analyze the mechanism, and the results show that the active C3-Fe-N local coordination microenvironment at the interface not only improves the water decomposition behavior, but also provides an in-depth understanding of the local interface geometry / electronic structure for improving the electrocatalytic activity.

[0020] The present invention adopts a simple hydrothermal reaction to quickly prepare the catalyst, which has low cost and high efficiency. BRIEF DESCRIPTION OF THE DRAWINGS

[0021] Figure 1 TEM images of the 0.8-C-Fe-N single-atom electron bridge (a, b); HR-TEM (c), dark-field HR-TEM image (d); magnified three-dimensional (3D) image of the single iron atom (SA) in 0.8-C-Fe-N (e); SAED image (f) and energy spectrum analysis image (g) of 0.8-C-Fe-N;

[0022] Figure 2 In the figure, a is the XRD pattern of C, 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe and 0.8-C-Fe-N (C-Fe-N SAEBs); b is the Raman result of C, 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe and 0.8-C-Fe-N (C-Fe-N SAEBs);

[0023] Figure 3In the figure, a is the OER polarization curve of C, 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and RuO2; b is the Tafel slope of C, 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and RuO2; c is the HER polarization curve of C, 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and Pt / C; d is the Tafel slope of C, 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and Pt / C;

[0024] Figure 4 The long cycle stability results of 0.8-C-Fe-N were measured by chronoamperometry.

[0025] Figure 5 a is the electronic structure distribution under theoretical calculation; b is the Fe K-edge X-ray absorption near-edge structure (XANES) spectrum of the target catalyst 0.8-C-Fe-NSAEB and the controls Fe foil, Fe2O3, FeO and FePc. DETAILED DESCRIPTION

[0026] The present invention provides a method for preparing a carbon-iron-hybrid carbon catalyst, comprising the following steps:

[0027] The carbon ball material, the iron source, the surfactant and the first solvent are mixed and subjected to a first hydrothermal reaction to obtain a carbon-iron product;

[0028] The carbon-iron product, a nitrogen source, a carbon source and a second solvent are mixed and subjected to a second hydrothermal reaction to obtain a carbon-iron-hybrid carbon catalyst.

[0029] In the present invention, unless otherwise specified, the required raw materials or reagents are commercially available products well known to those skilled in the art.

[0030] The present invention mixes a carbon ball material, an iron source, a surfactant and a first solvent, and performs a first hydrothermal reaction to obtain a carbon-iron product.

[0031] The present invention has no special limitation on the carbon ball material, and any commercially available product known in the art may be used; in the embodiment of the present invention, the carbon ball material is specifically sourced from SIGMA-ALDRICH, Co., and the model number is MKCQ2236.

[0032] In the present invention, the iron source preferably includes ferric chloride.

[0033] In the present invention, the surfactant preferably includes hexadecyltrimethylammonium bromide or polyvinylpyrrolidone; the first solvent is preferably ethylene glycol. The present invention has no special limitation on the amount of the first solvent, which can be adjusted according to actual needs to ensure smooth reaction.

[0034] In the present invention, the mass ratio of the carbon ball material, the iron source and the surfactant is preferably 0.05-0.2:0.3-1.6:0.15-0.6, more preferably 0.08-0.15:0.5-1.2:0.2-0.5, and further preferably 0.1:0.8:0.3.

[0035] The present invention preferably dissolves the carbon source in the first solvent under stirring conditions, stirs for 6 hours, adds a surfactant and an iron source to the resulting mixed solution, stirs for 1 hour at 40° C., and then performs a hydrothermal reaction in a polytetrafluoroethylene-lined stainless steel autoclave.

[0036] In the present invention, the temperature of the first hydrothermal reaction is preferably 160 to 200° C., more preferably 170 to 190° C., further preferably 180° C., and the time is preferably 6 to 12 h, more preferably 8 to 10 h.

[0037] After completing the first hydrothermal reaction, the present invention preferably washes the obtained product twice with ethanol and dries it in an oven at 60°C overnight to obtain a carbon-iron product, which is an iron atom-modified carbon sphere structure formed by atomically dispersed iron embedded in the surface of the carbon sphere.

[0038] After obtaining the carbon-iron product, the present invention mixes the carbon-iron product, a nitrogen source, a carbon source and a second solvent, and performs a second hydrothermal reaction to obtain a carbon-iron-hybrid carbon catalyst.

[0039] In the present invention, the nitrogen source preferably includes dicyandiamide; the carbon source preferably includes glucose or sucrose. The second solvent is preferably ethylene glycol. The present invention has no special limitation on the amount of the second solvent, which can be adjusted according to actual needs to ensure the smooth progress of the reaction.

[0040] The present invention utilizes a carbon source to obtain shell nitrogen-doped carbon, thereby constructing an atomic-level interface C-Fe-N microstructure. At the same time, the shell nitrogen-doped carbon protects metallic iron active species and promotes carrier migration during the electrochemical reaction.

[0041] In the present invention, the mass ratio of the carbon-iron product, the nitrogen source and the carbon source is preferably 0.025-0.1:0.05-0.2:0.2-0.8, more preferably 0.03-0.08:0.08-0.15:0.3-0.6, and further preferably 0.05:0.1:0.4.

[0042] The present invention preferably mixes the carbon-iron product with a carbon source and a nitrogen source in a second solvent, stirs the resulting solution continuously at 40° C. for 2 h, and transfers the resulting mixed solution to a Teflon-lined stainless steel autoclave for a second hydrothermal reaction.

[0043] In the present invention, the temperature of the second hydrothermal reaction is preferably 160 to 200° C., more preferably 170 to 190° C., further preferably 180° C., and the time is preferably 2 to 6 hours, more preferably 4 to 5 hours.

[0044] After completing the second hydrothermal reaction, the present invention preferably washes the obtained product with ethanol twice and dries it in an oven at 60° C. overnight to obtain a carbon-iron-hybrid carbon catalyst.

[0045] The present invention provides a carbon-iron-hybrid carbon catalyst prepared by the preparation method described in the above technical scheme.

[0046] The present invention provides the use of the carbon-iron-hybrid carbon catalyst described in the above technical solution in electrocatalytic water decomposition. The present invention has no special limitation on the method of the application, and the application can be carried out according to methods well known in the art.

[0047] The technical solutions provided by the present invention are described in detail below in conjunction with the embodiments, but they should not be construed as limiting the protection scope of the present invention.

[0048] Example 1

[0049] Under magnetic stirring, 0.1 g of carbon spheres (SIGMA-ALDRICH, Co; MKCQ2236) were dissolved in 40 mL of ethylene glycol. After stirring for 6 h, 0.3 g of CTAB and 0.8 g of FeCl3·6H2O were added to the resulting mixture, which was stirred at 40 °C for 1 h. The resulting homogeneous solution was transferred to a polytetrafluoroethylene-lined stainless steel autoclave at 180 °C for hydrothermal reaction for 8 h. The resulting product was washed twice with ethanol and dried in an oven at 60 °C overnight to obtain the intermediate product 0.8-C-Fe;

[0050] 50 mg of the prepared 0.8-C-Fe was mixed with 0.4 g of glucose and 0.1 g of dicyandiamide in 40 mL of ethylene glycol, and the resulting solution was continuously stirred at 40 °C for 2 h. The mixed solution was transferred to a Teflon-lined stainless steel autoclave and heated at 180 °C for 4 h. The product was washed twice with ethanol and dried in an oven at 60 °C overnight to obtain a catalyst, recorded as 0.8-C-Fe-N.

[0051] Example 2

[0052] The only difference from Example 1 is that 0.3 g of FeCl3·6H2O is added and the obtained intermediate product is recorded as 0.3-C-Fe.

[0053] Example 3

[0054] The only difference from Example 1 is that 0.5 g of FeCl3·6H2O is added and the intermediate product obtained is recorded as 0.5-C-Fe.

[0055] Characterization and performance testing

[0056] Figure 1 TEM images of 0.8-C-Fe-N single atom electron bridge (a, b); HR-TEM (c), dark field HR-TEM (d); magnified three-dimensional (3D) image of single iron atom (SA) in 0.8-C-Fe-N (e); SAED image (f) and energy spectrum analysis (g) of 0.8-C-Fe-N; the results show that metallic iron exists in the target catalyst and no obvious iron metal phase is generated. Moreover, with carbon sphere as the core, single iron atoms are embedded on the surface of carbon sphere, and then the outer shell is coated by nitrogen-doped carbon to form C-Fe-N chemical bonds; the inner and outer layers are carbon materials, and the core-shell structure is obtained by coating.

[0057] Figure 2 In the figure, a is the XRD pattern of C (carbon sphere in Example 1), 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe and 0.8-C-Fe-N (C-Fe-N SAEBs); b is the Raman result of C, 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe and 0.8-C-Fe-N (C-Fe-N SAEBs); Figure 2 As can be seen from a, there is no obvious characteristic peak of metallic iron in the 0.8-C-Fe-N catalyst, indicating that metallic iron distributed at the atomic level exists in an amorphous state in the catalyst; Figure 2 As can be seen in b, after comparison, the target catalyst 0.8-C-Fe-N exhibits larger defects.

[0058] Figure 3 In the figure, a is the OER polarization curves of C (carbon ball in Example 1), 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and commercially available RuO2 (SIGMA-ALDRICH, Co.); the results show that the target product 0.8-C-Fe-N has a lower overpotential and exhibits significant electrochemical activity.

[0059] Figure 3 b is the Tafel slope of C (carbon sphere in Example 1), 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and commercially available RuO2. The results show that the target product 0.8-C-Fe-N has better electrochemical OER reaction kinetics.

[0060] Figure 3 Where c is C (carbon sphere in Example 1), HER polarization curves of 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and Pt / C. The results show that the target product 0.8-C-Fe-N has a lower overpotential and exhibits significant electrochemical activity.

[0061] Figure 3 Where d is the Tafel slope of C (carbon sphere in Example 1), 0.3-C-Fe, 0.5-C-Fe, 0.8-C-Fe, 0.8-C-Fe-N and Pt / C. The results show that the target product 0.8-C-Fe-N has better electrochemical HER reaction kinetics.

[0062] Figure 4 The long cycle stability of 0.8-C-Fe-N was measured by chronoamperometry. After 50 h of cycle testing at a voltage of 1.612 V vs. RHE, Figure 4 It can be seen that the current density did not decay significantly, which further demonstrated that the catalyst had significant stability.

[0063] Figure 5 In the figure, a is the electronic structure distribution under theoretical calculation; b is the Fe K-edge X-ray absorption near-edge structure (XANES) spectrum of the target catalyst 0.8-C-Fe-NSAEBs and the control materials Fe foil, Fe2O3, FeO and FePc, revealing that the catalyst 0.8-C-Fe-N of the present invention has a unique carbon-iron-nitrogen interface chemical bond structure.

[0064] The above is only a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principle of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A method for preparing a carbon-iron-hybrid carbon catalyst, characterized in that: The following steps are involved: The carbon ball material, the iron source, the surfactant and the first solvent are mixed and subjected to a first hydrothermal reaction to obtain a carbon-iron product; The carbon-iron product, a nitrogen source, a carbon source and a second solvent are mixed and subjected to a second hydrothermal reaction to obtain a carbon-iron-hybrid carbon catalyst.

2. The preparation method according to claim 1, characterized in that: The iron source includes ferric chloride; the surfactant includes hexadecyltrimethylammonium bromide or polyvinylpyrrolidone.

3. The preparation method according to claim 1 or 2, characterized in that: The mass ratio of the carbon ball material, the iron source and the surfactant is 0.05-0.2:0.3-1.6:0.15-0.

6.

4. The preparation method according to claim 3, characterized in that: The temperature of the first hydrothermal reaction is 160-200° C., and the time is 6-12 hours.

5. The preparation method according to claim 1, characterized in that: The nitrogen source includes dicyandiamide; the carbon source includes glucose or sucrose.

6. The preparation method according to claim 5, characterized in that: The mass ratio of the carbon-iron product, the nitrogen source and the carbon source is 0.025-0.1:0.05-0.2:0.2-0.

8.

7. The preparation method according to claim 6, characterized in that: The temperature of the second hydrothermal reaction is 160-200° C., and the time is 2-6 hours.

8. The carbon-iron-hybrid carbon catalyst prepared by the preparation method according to any one of claims 1 to 7.

9. Use of the carbon-iron-hybrid carbon catalyst according to claim 8 in electrocatalytic water decomposition.